Determinación de Brucella spp. en leche en hatos ganaderos en zona sur de la Provincia de Los Ríos - Vera García, Daniela Dayanara (2023)
Brucellosis worldwide is an infectious, acute, or chronic disease. Although various programs have been implemented for many years to control and eradicate bovine brucellosis, bovine brucellosis is present in almost all South American countries. It is a zoonotic disease with enormous economic consequences and a delicate public health problem. In Ecuador there is a high rate of the disease; In humans it is transmitted through infected animals, for this the study will be carried out in the province of Los Ríos. The objective of this research work was determination of brucella spp in milk in livestock herds in the southern zone, where 66 milk samples were taken corresponding to 66 farms which were found distributed in 4 cantons belonging to the southern zone of the province. of the rivers (Babahoyo, Vinces, Palenque, Baba). Positive cases of Brucella spp were evaluated using the non-parametric square chip test. The cases were 4 positives, which represents 6.06%. It should be noted that the majority of positive cases were Vinces with 3%, while Baba had 1 positive case, which is 1.5%, followed by Babahoyo with 1.5% brucellosis and obtaining zero positive cases in the Palenque area.